PENGEMBANGAN E-BOOK BERBASIS FLIPBOOK UNTUK MENINGKATKAN HASIL BELAJAR IPAS SISWA KELAS V SD NEGERI 29 MANGGAM - Sukimin, Sukimin; Mashudi, Mashudi; Erlina, Erlina (Universitas Tanjungpura, 2025)
This research aims to develop a flipbook-based e-book to improve the learning outcomes of IPAS in grade V of SD Negeri 29 Manggam. This research uses the Research and Development (R&D) method with the ADDIE model. The subjects of the study were 22 students. Data collection techniques through observation, interviews, questionnaires, and tests. Data were analyzed descriptively, quantitatively, and qualitatively. The results of the study showed that the flipbook-based e-book developed had a validity level with a score of 89.33% from media experts, 92% from material experts, and 94% from linguists with a very high category. The practicality aspect obtained a score of 83.33% in the small group test and 97.08% in the large group test with the very practical category. The effectiveness aspect showed an increase in student learning outcomes with an N-gain value of 0.73 in the small group and 0.76 in the large group with a high category. Thus, flipbook-based e-books have proven to be valid, practical, and effective in improving student learning outcomes and being used as an innovative learning medium in the learning process.